A review of the defective TiO2 materials-based photocatalysis for environmental remediation: exploring the nexus between light wavelength and energy consumption - Nawaz, Rab; Marlia, Mohd Hanafiah; Zaini, Sakawi; Baki, Zahed Abdel; Sumaiya, Zainal Abidin; Muzammil, Anjum; Aznan Fazli, Ismail; Arshad, Ushtar (Elsevier, 2025)
Given the growing need to minimise emissions in order to combat climate change and the apparent association between electrical energy (EE) consumption and emissions, an inclusive analysis of the link between the wavelength of light and the EE consumption by defective titanium dioxide (D-TiO2) nanomaterials (NMs) could be extremely useful. An explicit understanding of the nexus between the energy consumption by D-TiO2 NMs–primarily EE–and the wavelength of light driving the oxidative degradation of organic compounds remain elusive. This review paper presents the analysis of the EE consumed by the D-TiO2 NMs at different wavelengths and the corresponding treatment cost (T-cost) for the oxidative degradation of four different organic compounds: pesticides (PES), organic dyes (ODs), phenolic compounds (PCs), and pharmaceuticals (PMs). The quantity of EE consumed was estimated using a reliable scale-up metric proposed by IUPAC. According to the analysis, the EE consumption increases by ~100 %, or 2.75 kWh/m3 for every nm, when the wavelength is extending from the UV (λ < 400) to the visible range (λ > 400 nm). Even while some D-TiO2 NMs improved energy efficiency and decreased EE consumption to less than 5 kWh/m3 , the values are still higher than those of a traditional treatment facility. To lower EE consumption and increase the energy efficiency of D-TiO2 NMs for environmental remediation, techniques like matching the spectrum of light with that of the pollutant and D-TiO2 NMs, light on and off modulation, and the development of hierarchical structures can be implemented.